Distribuição espaço-temporal e ecologia trófica de Stellifer brasiliensis (Schultz, 1945) na zona de arrebentação de duas praias adjacentes ao estuário do Rio Paraíba, PB, Brasil - Amorim, Ana Luisa Araújo de (2019)
This study investigates the spatial and temporal (seasonal and lunar cycles) influences on the distribution and diet of ontogenetic phases (juvenile, subadult and adult) of Stellifer brasiliensis in Costinha and Miramar beaches, at northeast Brazil. For that, beach seine hauls were monthly conducted from May 2014 to April 2015 at the surf zone of both beaches. These beaches were chosen because of their different exposures to the estuarine water. In May and July 2014, samples were taken, according to lunar phases in Miramar beach. The distribution and diet of S. brasiliensis showed a clear spatial variation. Temporally, the distribution was affected by the seasonal cycle, but with no lunar influence, while the diet was influenced by both temporal scales. The variation in the distribution of S. brasiliensis was governed by the turbidity. This species seems to prefer less turbidity habitats, showing abundance significantly high in Miramar beach. In general, diet of S. brasiliensis was composed mainly by crustaceans as Gammaridea and Calanoida. Variations on the trophic guild of this specie were detected as ontogenetic phases changed. Juveniles feed mainly on zooplankton, while subadults and adults prefer benthonic preys. Diet overlaps were observed in the consumption of Calanoida and Gammaridea in both temporal analyses, mainly between juveniles and subadults. The surf zone of Miramar and Costinha are important habitats for the early life stages of S. brasiliensis, working as a nursery ground for this specie. The occurrence of micro plastics in the stomachs of these three ontogenetic phases, shows the needs of efficient managements of theses habitats which were used by this and other species during most part of their life cycle.